Relative contribution of the ocean-air heat exchange and advective heat transport to the increase of the Barents Sea water temperature in the early 21st century - A. A. Sumkina; A. V. Smirnov; K. K. Kivva; V. V. Ivanov; А. А. Сумкина; А. В. Смирнов; К. К. Кивва; В. В. Иванов (Государственный научный центр Российской Федерации Арктический и антарктический научно-исследовательский институт, 2024)
The annual water temperature in the major water masses of the Barents Sea (BS) has significantly increased since the early 2000s. Advective heat transport from the neighboring water areas and heat exchange through the sea surface are the major factors, which shape the hydrological conditions in the BS. The paper estimates the contributions of heat exchange at the sea-atmosphere boundary and advective heat transport to changes in the average water temperature of the BS for the entire sea area. The average annual heat balance of the BS is calculated using atmospheric and oceanic reanalysis data. The change in the average temperature of the BS water is estimated taking into account the heat consumption for ice melting. The average surface heat balance from 1993 to 2018 was negative throughout the entire sea area: –70…–100 W/m2 in the south and –10…–20 W/m2 in the north. The advective heat supply was calculated for 9 straits with neighboring water areas. The determining source of advective heat is the influx of Atlantic waters from the Norwegian Sea between Cape Nordkapp and Bear Island. An average of 40.8 TW of advective heat is supplied through this margin. The calculations showed the predominance of annual heat influx due to advection over heat loss from the sea surface. This excess heat influx resulted in an estimated increase in the water temperature of the BS from 1993 to 2018 at a rate of 0.28 °C per year (taking into account the heat consumption for ice melting). In conclusion, it can be argued that the analysis has validated the hypothesis proposed in the article about compensation of heat losses from the surface of the BS by advective heat flow. The hypothesis is quantitatively confirmed by calculations on a simple box model (with an accuracy of up to an order of magnitude) based on atmospheric and oceanic reanalysis data. The ERA5 and GLORYS12V1 reanalysis data reliably describe the basic patterns of observed variability of ocean, sea ice and atmospheric parameters in the Barents Sea. С начала 2000-х ...